ANALISIS KRITIS TERHADAP KHUTBAH IDUL FITRI OLEH USTADZ DR. AGUS HERMANTO MHI - Dandi, Rakha (BASA Journal of Language & Literature, 2024)
The Eid al-Fitr sermon is one of the important moments in the Islamic religious calendar which is celebrated by Muslims around the world. Eid al-Fitr sermons are lectures delivered by religious leaders at mosques or other places of worship on Eid al-Fitr, after carrying out Eid prayers in congregation. This sermon has the aim of conveying religious messages and inspiring Muslims to increase their faith and piety. Critical analysis also reveals that the authenticity of the sermon is an important concern. Some sermons contain references that are unclear and can lead to different interpretations. In addition, choosing the right language and rhetoric has proven to be an important factor in the effectiveness of the sermon to convey messages clearly and move the congregation to act positively.